Facies analysis and fluid inclusion studies of the Messinian evaporites, Calabria, Southern Italy - Cipriani, Mara; Critelli, Salvatore; Costanzo, Alessandra; Dominici, Rocco (Università della Calabria, 2020)
Messinian salinity crisis (MSC) is, from about 30 years, one of the most important and debated topic in the scientific community, both in environment and economic field. In this context, Calabrian evaporite deposits, poorly investigated in the past, offer an interesting opportunity to expand the knowledge because they confirm and increase the models created for other Mediterranean basins, and add important information on the main halite and gypsum facies. In this regard, saline evaporitic facies outcropping in the Crotone, Catanzaro and Ionic Basins were investigated using a multidisciplinary approach from classical petrography, to the study of fluid inclusions (FIs) to isotopic geochemistry. (A) The halite samples from the Crotone Basin have highlighted three primary facies; two known in the literature as banded and white while the third, never observed before, called in this work transparent. The transparent facies seems recrystallized but the analyses conducted show instead a primary origin. The three facies form in different environment and with a dissimilar deposition rate (fast or slow) due to pycnocline oscillation (daily or seasonal). Pycnocline oscillations can explain the different temperature of homogenization found within the FIs (from +20° to +33°C). The facies form in a hybrid brine (salinity av. ̴ 26.2 eq. wt% NaCl) enriched in Ca-Mg-Na-K-Cl elements, regardless of their deposition rates. During their fluid inclusions testifying plastic and ductile deformations that don’t remove primary features, demonstrating low recrystallization during burial process. Moreover, isotopic data attribute these facies at the second step of the MSC (5.6-5.5 Ma) during Halite deposition stage in the Mediterranean Basin. (B) The selenite samples from the Catanzaro Trough belong to banded and giant facies. The crystals record middle-frequency climatic oscillation between the depositional cycles and high-frequency climatic oscillation (seasonal) between cloudy and clear microfacies observed within the crystals. These microfacies testify a different brine condition associated with seasonal variation: cloudy intervals form during continental water inflow in the humid phase (Mg and Ca as dominant elements and low salinity values - av. ̴ 3 eq. wt% NaCl), while, clear intervals form in marine water during the arid phase (Na, K and Cl as dominant elements and high salinity values - av. ̴ 21.5 eq. wt% NaCl). Isotopic data attribute these facies at the third step of the MSC (5.5-5.3 Ma) placing, for the first time, the formation of the giant facies at the Upper Gypsum stage in the Mediterranean Basin. (C) The analyses conducted on the gypsum deposit from the Ionian Basin have shown that these crystals do not display primary features. This deposit is an olistostrome. The isotopic data confirm secondary origin attributing these facies at the second step of the MSC (5.5-5.3 Ma) during the Resedimented Lower Gypsum deposition stage in the Mediterranean Basin. The data obtained from the study of the Calabrian Messinian deposits indicate a surprising variety and diversity of evaporitic facies. In this work, it emerges that the formation of, crystals trap primary FIs and microalgae (blue, green and yellow). Primary FIs and organic matters, associated with secondary the different facies is strongly conditioned by climate (wet/arid) and intrinsic characteristics of the basin (depth, arrival of continental water flows etc.) which promote the development of one facies rather than of another.
Università della Calabria Dipartimento di Biologia, Ecologia e Scienze della Terra (DiBEST). Dottorato in Scienze ed Ingegneria per l'Ambiente, le Costruzioni e l'Energia (SIACE) Ciclo XXXII
Keywords: Petrografia